High quantum yield Ag2S quantum dot@polypeptide-engineered hybrid nanogels for targeted second near-infrared fluorescence/photoacoustic imaging and photothermal therapy. Issue 5 (21st December 2017) - Zhao, Dong-Hui; Yang, Jie; Xia, Rui-Xue; Yao, Ming-Hao; Jin, Rui-Mei; Zhao, Yuan-Di; Liu, Bo
Abstract : We developed a new hybrid nanogel system for targeted second near-infrared fluorescence, photoacoustic imaging, and photothermal therapy of cancer. Abstract : A high quantum yield (4.3%) hybrid nanogel system based on engineered polypeptides and Ag2 S quantum dots has been developed as a multifunctional diagnostic and therapeutic agent for targeted second near-infrared fluorescence, photoacoustic imaging, and photothermal therapy.